FACTORS AFFECTING SMP/MTs STUDENTS'MOTIVATION TO GO INTO VOCATIONAL SCHOOLS IN SLEMAN DISTRICT - Kusworo, Kusworo; Soenarto, Soenarto (Jurnal Pendidikan Teknologi dan Kejuruan, 2016)
<div style="text-align: justify; color: #222222; font-family: Tahoma, Verdana, Arial, Helvetica, sans-serif; font-size: 12px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: 2; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff;"> This research aims to find out (1) motivation, (2) factors affecting motivation and (3) the most dominant factor affecting the motivation of Junior High School (SMP / MTs) students to Vocational Schools. This research belongs to cross-sectional survey. The population of this research is 12.037 of Grade VIII students from122 SMP/MTs at Sleman District. The research sample is 338 students who are taken randomly and proportionally. The instrument used is questionnaire with likert-scale and rating-scale. Data analysis techniques used are descriptive analysis, regression analysis and partial correlation analysis. Research results show that: (1) motivation of SMP/MTs students to go into Vocational School is good, the average is 73.40%; (2) factors affecting the motivation are social economic status of student's parents, mass media, student's environment, and students' individual characteristics with 72.5% and the rest which is 27.5% is affected by other factors; (3)the most dominant factor is students' individual characteristics, and then followed by mass media factor, social economic status of students' parents and students' environment.